The role of vitamin D and E in dysmenorrhea: a narrative review - Cencelewicz, Katarzyna; Bździuch, Patrycja; Pieniążek, Barbara; Domańska, Aleksandra; Pijas, Natalia; Piekarz, Daria (Quality in Sport, 2026)
Background. Dysmenorrhea, one of the most common gynecological problems, significantly reduces patients’ quality of life. Standard therapy is based on the use of nonsteroidal anti-inflammatory drugs (NSAIDs) and hormonal contraceptives, however it is associated with adverse effects. Alternative treatment methods are being sought, including vitamin supplementation, particularly vitamin D and E. Aim. The aim of this study was to evaluate the role of vitamin D and E supplementation in dysmenorrhea. Material and methods. In March 2026, the PubMed database was searched. The following strategies were applied: (Dysmenorrhea OR "menstrual pain") AND ("Vitamin D" OR cholecalciferol OR "vitamin D3" OR "25-hydroxyvitamin D" OR 25(OH)D) and (Dysmenorrhea OR "menstrual pain") AND ("Vitamin E" OR tocopherol OR alpha-tocopherol). Studies published in English within the last 10 years were included. After screening titles and abstracts, full-text analysis was performed. Ultimately, 12 publications were included. Results. An association between vitamin D levels and the severity of menstrual pain was demonstrated, and supplementation led to symptom reduction. Beneficial effects were also observed with the combined use of vitamins D and E, suggesting a possible synergistic effect. The results regarding vitamin E are inconsistent - some studies indicate its effectiveness, particularly in combination with other compounds (e.g., omega-3 fatty acids or vitamin C), which may be related to its antioxidant properties. However, not all studies confirm this relationship. Conclusions. Vitamin D and E supplementation may be an effective adjunct in the treatment of dysmenorrhea. However, further studies on larger populations are required.